Síndrome de Burnout académico en estudiantes universitarios durante el periodo de pandemia por la Covid-19 del 2020 al 2022: Academic Burnout syndrome in university students during the period of the Covid-19 pandemic from 2020 to 2022 - Zambrano-Díaz, Marisol (2024)
Objetive: to determine the ABS levels of university students, in addition to quantitatively describing the behavior of the analyzed SBA dimensions. Methods: The methodology used was descriptive, through data collection through virtual questionnaires. The surveys were carried out under informed consent, using the Maslach Burnout Inventory Student Survey (MBI-SS) as a measurement instrument. Results: The data obtained were analyzed with the statistical program named IBM SPSS version 26, finding a high level of reliability (Cronbach's Alpha of 0.86). The results on the study population indicated that their High ABS levels increased from 2020 to 2021, from 3% to 8%; lowering this percentage to 5% by 2022; while Medium ABS levels presented a moderate variation of 93%, 82% and 87% in the years 2020, 2021 and 2022 respectively. Students with Low ABS levels had an increase from 2020 to 2021, from 4% to 10%; lowering this percentage to 8% by the year 2022. In relation to the dimensions of the ABS, indicated that the students presented a higher Emotional Exhaustion between 2020 and 2021, with a downward trend in 2022. In addition, they presented higher levels of Cynicism in 2021, compared to the years 2020 and 2022; Their levels of Academic Self-Efficacy remained moderately stable throughout the pandemic period from 2020 to 2022. Conclusion: that more than 80 percent of university students presented average levels of ABS from 2020 to 2022, with 2021 being the year with the highest levels of the ABS.